1985
DOI: 10.1073/pnas.82.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an additional class of C3-binding membrane proteins of human peripheral blood leukocytes and cell lines.

Abstract: Proteins binding the third component of complement (C3) were isolated by affinity chromatography from surface-labeled solubilized membranes of human peripheral blood cells and cell lines. The isolated molecules were subjected to NlttodSO4/PAGE, and autoradiographs of these gels indicpe. that C3-binding [1][2][3][4]. This molecule has a number of interesting structural and regulatory features (1, 2, 5-11), including an unusual polymorphism in which there is an -60,000 difference in Mr among the three recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 30 publications
4
102
0
Order By: Relevance
“…CD46, CD55 and CD59 are important cell surface molecules which protect autologous cells from injury by complement [1,2,13,14]. Among these molecules, up-regulation of CD59 was ®rst shown on the glomerular cells of lupus nephritis patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD46, CD55 and CD59 are important cell surface molecules which protect autologous cells from injury by complement [1,2,13,14]. Among these molecules, up-regulation of CD59 was ®rst shown on the glomerular cells of lupus nephritis patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane cofactor protein (MCP, CD46) is a cell surface glycoprotein which acts as a cofactor for the factor I-mediated cleavage of the activated complement components C3b/C4b [1,2]. This molecule is thought to be crucial in protecting autologous cells against attack by the complement system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that after antigen binding to BCR, the BCR itself could form a platform for activation of the classical complement pathway which resulted in the deposition of C3 fragments on the antigen which would presumably allow direct binding with CR1/2 and provide co-stimulatory signals into the B cell in a cell bound amplification loop (Manderson et al, 2006;Rossbacher and Shlomchik, 2003). It is also worth remembering that CR2 was shown to bind to sepharose bound inactive C3 (Cole et al, 1985). Thus, the ability of fB/C2 deficient sera to cause down regulation of hCR2 expression (Figure 6) demonstrates that the natural generation of inactive C3 could provide ligand to interact with CR2 as well as suggesting that the generation of C3d is not necessarily required for this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…CR2, in both mouse and man, binds with high affinity to the C3 breakdown fragment C3d (as well as iC3b and C3dg, (Cole et al, 1985;Farries et al, 1990;Iida et al, 1983;Kalli et al, 1991;Molina et al, 1994;Weis et al, 1984) which remains covalently bound to complement activating surfaces or antigen (Law and Dodds, 1997). Consistent with a key role for C3 fragments in amplifying the immune response via the CR2/CD19, C3 −/− mice have weak humoral immune responses and defects in germinal center formation, Wessels et al, 1995).…”
Section: Introductionmentioning
confidence: 94%